2016
DOI: 10.14202/vetworld.2016.231-234
|View full text |Cite
|
Sign up to set email alerts
|

Peperomia pellucida leaf extract as immunostimulator in controlling motile aeromonad septicemia due to Aeromonas hydrophila in red hybrid tilapia, Oreochromis spp. farming

Abstract: Aim:This study was revealed the potential of Peperomia pellucida leaf extract as an immunostimulator agent in controlling motile aeromonad septicemia due to Aeromonas hydrophila in red hybrid tilapia, Oreochromis sp.Materials and Methods:In the present study, minimum inhibitory concentration (MIC) of P. pellucida leaf extract against A. hydrophila was determined through two-fold microbroth dilution method. The plant extract was screening for its active compound using a gas chromatograph mass spectrometer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Furthermore, numerous investigations have pointed out the great antimicrobial potential of herbs as alternative biomedicine in aquaculture [45]. This review emphasizes its phytotherapeutic effect against aquaculture pathogenic bacteria in Malaysia (Table -2) [24,43,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Phytotherapeutic Agentsmentioning
confidence: 99%
“…Furthermore, numerous investigations have pointed out the great antimicrobial potential of herbs as alternative biomedicine in aquaculture [45]. This review emphasizes its phytotherapeutic effect against aquaculture pathogenic bacteria in Malaysia (Table -2) [24,43,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Phytotherapeutic Agentsmentioning
confidence: 99%
“…In the negative control group, granulocytes of tiger shrimp were 33.67% and increased to 34.33% after subjected to challenge tests. Immunostimulants agent is known to increase total hemocyte cells, granulocytes, semi-granulocytes, and hyaline cells [27].…”
Section: Hemocytes Profilementioning
confidence: 99%
“…In a study, Lee et al [73] revealed the potential of leaf extract of P. pellucida (mixed with fish pellets) as an immunostimulator in controlling motile aeromonad septicemia caused by Aermomonas hydrophila in Oreochromis spp. (red hybrid tilapia).…”
Section: Immunostimulatory Activitymentioning
confidence: 99%